Study on Exosomes Promoting the Osteogenic Differentiation of ADSCs in Graphene Porous Titanium Alloy Scaffolds - Sun, Xu; Yang, Shude; Tong, Shuang; Guo, Shu (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium and titanium alloys (Ti6Al4V and Ti) have been widely used in bone tissue engineering to repair maxillofacial bone defects caused by traumas and tumors. However, such materials are also bio-inert, which does not match the elastic modulus of bone. Therefore, different surface modifications have been proposed for clinical application. Based on the use of traditional titanium alloy in the field of bone repair defects, we prepared a compound Gr-Ti scaffold with ADSC-derived Exos. The results showed that Gr-Ti scaffolds have low toxicity and good biocompatibility, which can promote the adhesion and osteogenic differentiation of ADSCs. Exos played a role in promoting osteogenic differentiation of ADSCs: the mRNA levels of RUNX2, ALP, and Osterix in the Gr-Ti/Exos group were significantly higher than those in the Gr-Ti group, which process related to the Wnt signaling pathway. Gr-Ti scaffolds with ADSCs and ADSC-derived Exos successfully repaired rabbit mandibular defects. The bone mineral density and the bending strength of the Gr-Ti/Exos group was significantly higher than that of the Gr-Ti group. This study provides a theoretical basis for the research and development of new clinical bone repair materials.